Emerging role of RNA methyltransferase METTL3 in gastrointestinal cancer - Qiang Wang (Journal of Hematology & Oncology, 2020)
Abstract Gastrointestinal cancer, the most common solid tumor, has a poor prognosis. With the development of high-throughput sequencing and detection technology, recent studies have suggested that many chemical modifications of human RNA are involved in the development of human diseases, including cancer. m6A, the most abundant modification, was revealed to participate in a series of aspects of cancer progression. Recent evidence has shown that methyltransferase-like 3 (METTL3), the first identified and a critical methyltransferase, catalyzes m6A methylation on mRNA or non-coding RNA in mammals, affecting RNA metabolism. Abnormal m6A levels caused by METTL3 have been reported to be involved in different aspects of cancer development, including proliferation, apoptosis, and metastasis. In this review, we will shed light on recent findings regarding the biological function of METTL3 in gastrointestinal cancer and discuss future research directions and potential clinical applications of METTL3 for gastrointestinal cancer.